A role for actin in aging and apoptosis. (26th October 2005) - Gourlay, C.W.; Ayscough, K.R.
Abstract : The actin cytoskeleton is central to many cell processes including membrane trafficking and generation of cell polarity. We have identified a role for actin in cell death and in promoting longevity of the budding yeast, Saccharomyces cerevisiae . Aging in yeast appears to occur via an apoptotic-like pathway with changes including DNA fragmentation, loss of mitochondrial membrane permeability, increase in levels of ROS (reactive oxygen species) and exposure of phosphatidylserine in the outer leaflet of the plasma membrane. This pathway can be induced by alterations in actin dynamics, such that reduced dynamics correlates with increased levels of ROS and decreased viability. Conversely, increased actin dynamics correlates with low ROS levels and increased survival. Our current studies have focused on identifying pathways which couple changes in actin dynamics to cell death.